How to improve compression garment wear after burns: Patient and therapist perspectives. Issue 6 (September 2019) - Coghlan, Nicole; Copley, Jodie; Aplin, Tammy; Strong, Jenny
Highlights: Patients want access to more education including multimedia options such as the internet. Patients want access to peers for information however no clear peer support options. Patients want to be involved with all aspects of garment prescription. Occupational therapists expressed concern over patients accessing inappropriate information. Abstract: Background: Compression garments are a widely used intervention for the management of hypertrophic scar and recent research demonstrates the varied experiences of patients wearing compression garments. However, the patient and therapist perspective on how to improve the experience of wearing compression garments remains unexplored. Objective: To gain an understanding of the patient and therapist perspective of potential improvements to the provision of compression garments after burns. Method: A qualitative research design with an interpretive description approach was utilised in this study. Data was collected from patients through semi-structured interviews and a focus group and therapists by a focus group. Thematic analysis was completed to reveal the key themes across the data. Results: Two main themes were identified: "what patients want" and "access to professional development". The first theme "what patients want" described three suggested improvements including education, peer support, and increased participation in garment prescription. Conclusions: The reported patient and therapist perspectives highlight the need for further research into service improvement to enhance the patient experience of wearing compression garments after burns.